Preterm birth and air pollution: Critical windows of exposure for women with asthma - Mendola, Pauline (J Allergy Clin Immunol, 2016)
BACKGROUND: Ambient air pollutants may increase preterm birth (PTB) risk but critical exposure windows are uncertain. The interaction of asthma and pollutant exposure is rarely studied. OBJECTIVE: To assess the interaction of maternal asthma and air pollutant exposures in relation to PTB risk. METHODS: Electronic medical records for 223,502 U.S. deliveries were linked with modified Community Multiscale Air Quality model outputs. Logistic regression with generalized estimating equations estimated the odds ratio (OR) and 95% confidence intervals (CI) for PTB based on the interaction of maternal asthma and particulate matter <2.5 microns (PM(2.5)) and <10 microns (PM(10)), ozone (O(3)), nitrogen oxides (NO(x)), sulfur dioxide (SO(2)) and carbon monoxide (CO) per interquartile range. For each gestational week 23–36, exposures among women who delivered were compared to those remaining pregnant. Three-months preconception, whole pregnancy, weeks 1–28 and the last six weeks of gestation averages were also evaluated. RESULTS: Assessing PTB by gestational week, significant asthma interactions were sporadic before 30 weeks but more common during weeks 34–36 with higher risk among asthmatic mothers for NO(x), CO and SO(2) exposure and an inverse association with O(3) in week 34. Odds of PTB were significantly higher among asthmatics for CO and NO(x) preconception and early in pregnancy. In the last six weeks of pregnancy, PM(10) risk for PTB was higher among asthmatics. CONCLUSION: Asthmatic mothers may experience higher risk for PTB after exposure to traffic-related pollutants such as CO and NO(x) particularly for exposures three-months preconception and in the early weeks of pregnancy.